PUBLIC SPACE DAN PRIVATE SPACE - POSISI STRATEGIS PERPUSTAKAAN DALAM MENDUKUNG PEMBELAJARAN KOLABORATIF - Purwani Istiana (Jurnal Pustaka Ilmiah, 2015)
The library has the resources in the form of a library room that can be optimized to provide support to collaborative learning. Library as a public space open for anyone to come, move, and enjoy the facilities of library. Library room with the support of information and communication technology-enabled to support collaborative learning process. Limitations of classrooms available on formal and informal education supported by information and communication technologies to make the library into a public space that is appropriate as the choice of implementation of the learning process. The availability of private space in a library makes the library has the advantage not only of space and collaborative learning facilities, but also a pleasant experience for pemustaka. The library is a public space, also the private sphere that gives comfort pemustaka for collaborative learning both online and offl ine. The space is fl exible and responsive to the needs pemustaka become an important point in developing and optimizing the space available libraries.